Ну Бог с има! – Несколько наблюдений над формами творительного падежа множественного числа в говоре д. Варзуги - Pineda, David (Poljarnyj vestnik, 2002)
This paper attempts to give an overview of the different case endings found in the Instrumental Plural in the Northern Russian dialect of Varzuga on the Kola Peninsula, and looks at the situation in the neigh- bouring Russian dialects of Carelia and the Archangel district. Along with the Literary Russian ending [m'i], Varzuga uses the endings [my] (in nouns) and [ma] (in nouns, adjectives and pronouns). While [my] dominates in noun declension, [ma] is dominant in adjectives, and in possessive and demonstrative pronouns. These facts link the Varzuga dialect to Carelia, whereas Northern Archangel dialects do not use [my] at all, and reserve [ma] for adjectival and pronominal declension only.
Keywords: Russian; langauge; dialectology; instrumental case